Hydrodistillation of Trachelospermum jasminoides Lindl. flowers. An analysis of essential oil, hydrolate and polyphenols content of the process wastes. Issue 6 (1st November 2020) - Napoli, Edoardo; Dattilo, Sandro; Ruberto, Giuseppe
ABSTRACT: Trachelospermum jasminoides: (Lindl.) is a woody evergreen plant of the Apocynaceae family mainly used as ornamental/hedge plant. Its stems and leaves are used in traditional Chinese medicine with the name of ' Luoshiteng '. Although some studies have been devoted to the phytochemistry of luoshiteng, little is known about the chemical composition of its flowers. In this study, the volatile composition of the flowers of T. jasminoides has been studied. The Gas chromatographic – Mass spectrometry analysis (GC/FID-MS) of the essential oil and hydrolate allowed identifying 43 compounds with linalool as the main compound for both of them. Phytochemical investigation was completed by the High Performance Liquid Chromatography – Mass spectrometry (HPLC/DAD-ESI-MS) analysis of hydrodistillation wastes (liquid and solid) which revealed the presence of biologically active compounds such as chlorogenic acids and other polyphenols. This study contributes to the definition of the phytochemistry of T. jasminoides and provides the first data on the composition of the hydrodistillation wastes preparatory to their valorisation in the future.